Problems of recognition of judgments and other acts of unrecognized states in private international law - Abirbek, С.Т. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
This article deals with the problems of recognition of court decisions and other acts of unrecognized states in private international law. The relevance of this problem lies in the possibility of recognizing court decisions and other acts of unrecognized states, given that their status is not defined in accordance with international public law. Today, along with the application of the law of unrecognized states, the issues of recognition of their judgments or other acts are relevant, which by their nature are characterized as legal documents. Due to the fact that the status of these associations cannot be resolved in any way in the light of the norms of international public law, one cannot hide the fact that these actors exist and have all the main features of the state. A barrier to the exercise of the full right to be a state is the non-recognition by the world community. This article will be considered using a general and comparative legal analysis, with the help of which we will get answers to the possibility of recognizing court decisions and other acts of unrecognized states. In conclusion, this article proposes a set of recommendations for solving the problem posed, which will help to find the right direction regarding the recognition of court decisions and other acts of unrecognized states.